Đo lường mức lương đủ sống tối thiểu cấp tỉnh: Phương pháp Anker hiệu chỉnh sử dụng số liệu khảo sát hộ gia đình Việt Nam - Võ Tất , Thắng; Nguyễn Thiện , Nhân; Nguyễn Đông, Phong; Trương Thị Kiều , Nhung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
In Vietnam, the minimum wage remains low despite rising prices, inflation, and economic shocks. However, existing literature largely overlooks empirical analysis of the minimum living wage. This study utilizes data from the 2022 Vietnam Household Living Standards Survey (VHLSS 2022) with 9,392 households to propose a method for calculating the minimum living wage for a standard provincial household. The study develops an adjusted approach suitable for the Vietnamese context based on the GWLC (Anker) methodology. The research results confirm: (1) There is a significant discrepancy in the minimum living wage across provinces/cities, with the highest being in Hanoi at VND 18.880 million per household and the lowest in Lai Chau at VND 8.368 million per household; (2) The statutory minimum wage is significantly lower than the minimum living wage in most provinces, specifically 37.987% lower in Ho Chi Minh City and 36.277% lower in Hanoi compared to the minimum living wage.